House of cotton - Brashears, Monica (Flatiron Books, 2023)
"Nineteen years old, broke, and effectively an orphan, Magnolia doesn't have much to look forward to. She feels stuck and haunted: by her overdrawn bank account, by her predatory landlord, by the ghost of her late grandmother Mama Brown. One night while working at her dead-end gas station job, a mysterious, slick stranger named Cotton walks in and offers to turn Magnolia's luck around. He offers her a lucrative "modeling" job at his family's funeral home. Magnolia accepts. But despite things looking up, Magnolia's problems fatten along with her wallet. When Cotton's requests become increasingly weird, Magnolia discovers there's a lot more at stake than just her rent"--